2000
DOI: 10.1046/j.1365-2559.2000.01011.x
|View full text |Cite
|
Sign up to set email alerts
|

Trisomy 6 in Merkel cell carcinoma: a recurrent chromosomal aberration

Abstract: CISH seems to be a promising adjunctive method to diagnose Merkel cell carcinoma. Trisomy 6 should be investigated more closely in these cases, as has been done for chromosomes 1 and 11. Of particular interest would be identification of modifications in proto-oncogene(s) located on chromosome 6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 35 publications
2
21
0
Order By: Relevance
“…Trisomy of chromosome 6 is widely considered as recurrent chromosomal aberration in MCC, [26][27][28] which was the case also in our study. In 42% of the primary MCC samples analyzed by CGH, overrepresentation of all genomic material of chromosome 6 was observed.…”
Section: Discussionsupporting
confidence: 76%
“…Trisomy of chromosome 6 is widely considered as recurrent chromosomal aberration in MCC, [26][27][28] which was the case also in our study. In 42% of the primary MCC samples analyzed by CGH, overrepresentation of all genomic material of chromosome 6 was observed.…”
Section: Discussionsupporting
confidence: 76%
“…28,29,[48][49][50][51] Flow cytometry is useful if there is a history of or suspicion of coexisting lymphoma, as illustrated in our Patient 5.…”
Section: Ancillary Studies: Immunohistochemistrymentioning
confidence: 99%
“…11 In 1 study, trisomy 6 was observed in 47% of patients. 29 In another study, positive tyrosine-protein kinase Kit (c-Kit) status was reported in 95% of MCC tumors, 30 generating interest in the tyrosine kinase inhibitor imatinib, which initially was designed to target the breakpoint cluster region/ v-abl Abelson murine leukemia viral oncogene homolog (Bcr-Abl) fusion. However, Swick et al 31 suggest that its effectiveness may be limited, because no c-Kit-activating mutations were observed in their series.…”
Section: Etiologymentioning
confidence: 99%
“…For the evaluation of positivity, we followed the same approach by Gancberg et al [10], who regarded as trisomic the cases with more than 15% of nuclei showing three spots and monosomic those showing loss of one chromosome (one spot only) in more than 40% of cells. Internal control consisted of the use of chromosome 17 probes.…”
Section: Evaluation Of Positivitymentioning
confidence: 99%
“…Several cytogenetic alterations have been described in these neoplasms, especially involving chromosomes 1, 11, and 13 as well as losses of 4p15-pter and gains of 8q21-q22 in common with squamous cell carcinoma of the skin [13][14][15]. Trisomy of chromosome 6 is the most frequent cytogenetic change having been seen in 47% of cases using in situ hybridization [10,12].…”
Section: Introductionmentioning
confidence: 99%